The future of pain pharmacy: driven by need - Atkinson TJ; Gulum AH; Forkum WG (Dove Medical Press, 2016)
Timothy J Atkinson, Alev H Gulum, William G Forkum Veteran Affairs Tennessee Valley Healthcare System, Murfreesboro, TN, USA Background: Opioid prescribing has increased by ~400% over the past 20 years in the US and has been correlated with dramatic increases in accidental overdose-related deaths. Emerging evidence of serious dose-dependent side effects of opioid analgesics has led to recommendations from multinational pain societies and governments to decrease opioid doses and increase referrals to pain specialists. Demand for pain specialists of all types has increased; however, training programs for health care professionals struggle to satisfy this need. Objective: The purpose of this article is to highlight the role of clinical pharmacy specialists in pain management and to discuss available residency training programs and subspecialties within each program. Methods: We surveyed all eleven accredited pharmacy postgraduate year two (PGY-2) Pain and Palliative Care Residency programs in the US. Program information was derived from interviews with residency directors, current residents, program brochures, and residency Web sites. Data collected included core, elective, and longitudinal rotations, with the time frame dedicated to each experience. Primary practice areas, as well as inpatient vs outpatient focus, were also documented. Additionally, a review of the available literature was completed to determine the areas in greatest need for future pain specialists. Results: Pharmacy pain specialists have been referenced as highly effective additions to interdisciplinary pain management teams. Pharmacists provide expertise in complex pain medication management, which remains the primary focus of most chronic pain encounters. The PGY-2 programs surveyed differ considerably, with the majority providing significant emphasis to either acute pain management or palliative care with brief or limited exposure to chronic pain management. Four of the eleven programs require 2 months of chronic pain management; however, only two of the eleven programs identify chronic pain management as a primary practice setting. Discussion: Pain specialists in all fields are in high demand; however, the need for health care professionals specialized in chronic pain management probably exceeds that for professionals specialized in acute pain management and palliative care combined. This disparity between disease prevalence and specialty training programs is not reflected in the current residency training structure, nor have additional training programs arisen to fill this critical need. Conclusion: Health care systems will continue to struggle to meet the demands of patients with chronic pain until significant emphasis is placed on the education and training of health care professionals in this area. Clinical pharmacy should aim to meet this demand through the expansion of PGY-2 training programs and improved didactic education in pharmacy school that reflects the increased need for chronic pain specialists. Keywords: pain management, clinical pharmacists, pharmacy pain specialists, training programs